2022
DOI: 10.1093/mnras/stac716
|View full text |Cite
|
Sign up to set email alerts
|

Stellar collisions in globular clusters: the origin of multiple stellar populations

Abstract: Two generations of stars, G1 and G2, typically populate Galactic globular clusters (GCs). The origin of G2 stars is unclear. We uncover two empirical dependencies between GC characteristics, which can be explained by the formation of G2 Main-Sequence (MS) stars due to collision/merging of their primordial counterparts (G1). A similar genesis of both G2 stars and peculiar objects like LMXBs and millisecond pulsars is also implied. Indeed, we find a significant (at a confidence level $> 99,9{{\ \rm per\ c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
9
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 53 publications
2
9
0
1
Order By: Relevance
“…Another physical process that can lead to the formation of G2 stars over a short timescale, prior to gas expulsion from the clusters by the first supernovae, is stellar collisions (Sills et al 2002;Sills & Glebbeek 2010;Jiang et al 2014;Wang et al 2020). Collisions can still occur at later times, albeit at a lower rate (Kravtsov & Calderón 2021;Kravtsov et al 2022). Collisions not only set the relative fractions of the G1 and G2 stars, but they also alter the shape of the IMF of the G1 stars (Dib et al 2007;Kravtsov et al 2022).…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Another physical process that can lead to the formation of G2 stars over a short timescale, prior to gas expulsion from the clusters by the first supernovae, is stellar collisions (Sills et al 2002;Sills & Glebbeek 2010;Jiang et al 2014;Wang et al 2020). Collisions can still occur at later times, albeit at a lower rate (Kravtsov & Calderón 2021;Kravtsov et al 2022). Collisions not only set the relative fractions of the G1 and G2 stars, but they also alter the shape of the IMF of the G1 stars (Dib et al 2007;Kravtsov et al 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Collisions can still occur at later times, albeit at a lower rate (Kravtsov & Calderón 2021;Kravtsov et al 2022). Collisions not only set the relative fractions of the G1 and G2 stars, but they also alter the shape of the IMF of the G1 stars (Dib et al 2007;Kravtsov et al 2022). While more work is still needed in order to understand whether stellar collisions, particularly of low-mass stars, can lead to the chemical anticorrelations that are observed for GCs, Kravtsov et al (2022) present observational evidence that supports the scenario in which stellar collisions of G1 stars in the mass range ≈ (0.1-0.5) M ⊙ can lead to the formation of G2 stars in the mass range (0.5-0.9) M ⊙ .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Using this prescription of the IMF where implicitly IMF variations are driven by the gas-phase metallicity of the gas and by its density, they were able to recover the observed dependence of the slope of the IMF in the high stellar mass regime on the SFR (Gunawardhana et al 2011). More recently, Dib et al (2022) showed that allowing for variations of the IMFs, particularly in the regime of stellar masses around its peak can help explain the scatter that is observed between the fraction of first generation stars and the present-day slope of the mass function in globular clusters that has been recently presented by Kravtsov et al (2022). It is probably safe to say that more work is still needed in order to better quantify the level of IMF variations within galaxies, and to relate these variations to the physical conditions of the star forming gas.…”
Section: Comparison To the Observations Of Ultra-faint Dwarf Galaxiesmentioning
confidence: 99%